2013
DOI: 10.1155/2013/429862
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Younger Age at Onset in Breast Cancer Patients in Asia: An Age-Period-Cohort Analysis of Fifty Years of Quality Data from the International Agency for Research on Cancer

Abstract: Introduction. There is an established fact that Asian breast cancer patients are, on average, younger than their European counterparts. This study aimed to utilize the data from the Cancer Incidence in Five Continents I through XIII (published by the International Agency for Research on Cancer) to examine what contributes to the younger age at onset in the Asian population. Material and Methods. Data (number of breast cancer cases and corresponding population figures) for 29 registries in Europe and 9 registri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
24
0
2
Order By: Relevance
“…Also, the results from a 2016 study in Canada (21) and a 2017 Iranian study (22) confirm our findings. Some research has reported that the age of onset of breast cancer in women of the EMR and also Asian women is lower than their European and American counterpart (23). Breast cancer is a rare disease in young women, however the clinical and pathological outcomes are more aggressive than in older patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results from a 2016 study in Canada (21) and a 2017 Iranian study (22) confirm our findings. Some research has reported that the age of onset of breast cancer in women of the EMR and also Asian women is lower than their European and American counterpart (23). Breast cancer is a rare disease in young women, however the clinical and pathological outcomes are more aggressive than in older patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical carcinoma has become the fourth most common cancer in women in the world 1. The 5-year overall survival of cervical cancer is ~60% in all stages due to dramatic advances in screening and effective treatment 2.…”
Section: Introductionmentioning
confidence: 99%
“…Although the strongest associations with breast cancer were observed in younger women in our study, the case numbers for other tumor sites did not allow for stratified analyses by age. Considering that the incidence of lung cancer and CRC sharply increases with age and the average age at onset is slightly higher as compared with breast cancer, and the fact that breast cancer occurs at a generally younger age in Asian women with the highest rates apparent in those 45 to 50 years old (29), it is possible that the dynamics of our cohort are not yet conducive to detecting a significantly increased risk of CRC and lung cancer. This may particularly be the case if elevated levels of CRP, and the underlying processes contributing to these higher levels, have induction periods for carcinogenesis that vary by tumor type.…”
Section: Discussionmentioning
confidence: 98%